1998
DOI: 10.1128/aac.42.12.3251
|View full text |Cite
|
Sign up to set email alerts
|

The Oxazolidinone Linezolid Inhibits Initiation of Protein Synthesis in Bacteria

Abstract: The oxazolidinones represent a new class of antimicrobial agents which are active against multidrug-resistant staphylococci, streptococci, and enterococci. Previous studies have demonstrated that oxazolidinones inhibit bacterial translation in vitro at a step preceding elongation but after the charging ofN-formylmethionine to the initiator tRNA molecule. The event that occurs between these two steps is termed initiation. Initiation of protein synthesis requires the simultaneous presence of N-formylmethionine-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
0
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 474 publications
(210 citation statements)
references
References 26 publications
2
199
0
9
Order By: Relevance
“…Whether this reflects differences in the drugs or the biochemical systems remains to be resolved. In any case, there is mounting evidence suggesting that the oxazolidinones exert their influence through the positioning or accommodation of initiator fMet-tRNA on the ribosome, leading to the proposal that the site of action of oxazolidinones may in fact be the initiation phase of translation [162][163][164][165]. In support of this, Colca et al [156] also detected an oxazolidinone specific crosslink to tRNA; unfortunately, however, whether the species was the initiator-tRNA could not be determined.…”
Section: New Classes Of Translation Inhibitors; the Oxazolidinones Anmentioning
confidence: 62%
“…Whether this reflects differences in the drugs or the biochemical systems remains to be resolved. In any case, there is mounting evidence suggesting that the oxazolidinones exert their influence through the positioning or accommodation of initiator fMet-tRNA on the ribosome, leading to the proposal that the site of action of oxazolidinones may in fact be the initiation phase of translation [162][163][164][165]. In support of this, Colca et al [156] also detected an oxazolidinone specific crosslink to tRNA; unfortunately, however, whether the species was the initiator-tRNA could not be determined.…”
Section: New Classes Of Translation Inhibitors; the Oxazolidinones Anmentioning
confidence: 62%
“…In contrast, DuP 721 at 230 mM did not inhibit binding of fMet-tRNA to saltextracted Staphylococcus carnosus ribosomes in the presence of a natural mRNA from S. hyicus and E. coli initiation factors but exhibited a 50% inhibition of the release of fMet-puromycin [10]. These findings were recently challenged by Swaney et al, reporting that linezolid inhibits binding of fMet-tRNA to E. coli 30S ribosomal subunits and 70S ribosomes at IC 50 's of 110 and 130 mM, respectively [12]. These authors used kasugamycin as a reference inhibitor to inhibit binding of fMet-tRNA to the 30S preinitiation complexes [14].…”
Section: Do Oxazolidinones Block Formation Of a (Pre)initiation Complex?mentioning
confidence: 78%
“…Interference of oxazolidinones with initiation of translation was investigated in considerable detail in two recent studies [10,12]. According to a current model of translation initiation in eubacteria [13], mRNA and fMet-tRNA (formylmethionine-transfer RNA) bind in random order to 30S ribosomal subunits in the presence of initiation factors 1 and 3, giving rise to a 30S preinitiation complex.…”
Section: Do Oxazolidinones Block Formation Of a (Pre)initiation Complex?mentioning
confidence: 99%
“…Work on oxazolidinone inhibition of cell-free protein synthesis systems was problematic until it was shown that the final concentration of mRNA in the Escherichia coli S30 extract was critical in inhibition studies [6]. Recently studies with linezolid have demonstrated specific inhibition of translation initiation in that initiation complex formation using E. coli 30S subunits or 70S ribosomes was 50% inhibited by 110 M and 130 M of linezolid [9]. Similarly performed experiments in a Staphylococcus aureus cell-free protein synthesis assay also demonstrated that mRNA was required for linezolid inhibition of the initiation complex formation.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…We felt this was particularly important with the staphylococci and their propensity for resistance development which is well known. More recently the novel use of a spiral gradient plating technique has resulted in the isolation of S. aureus isolates which are resistant to eperezolid and linezolid [7,9,11]. Over 20 serial transfers in a drug gradient were required to produce one resistant S. aureus with a MIC of 32 mg/l for eperezolid and which was cross-resistant with linezolid.…”
Section: Resistance Developmentmentioning
confidence: 99%